XML:
<parent>
<pair>
<name>ABC</name>
<value>10</value>
</pair>
<pair>
<name>ABC</name>
<value>50</value>
</pair>
<pair>
<name>XYZ</name>
<value>30</value>
</pair>
</parent>
XSLT:
<xsl:template match="/">
<parent>
<xsl:for-each select="//parent/pair[not(name=preceding::pair/name)]">
<xsl:variable name="curName" select="name" />
<pair>
<name>
<xsl:value-of select="name"/>
</name>
<value>
<xsl:value-of select="sum(/parent/pair[name = $curName]/value)"/>
</value>
</pair>
</xsl:for-each>
</parent>
</xsl:template>
或者:
<xsl:key name="pair-by-name" match="parent/pair" use="name" />
<xsl:template match="/">
<parent>
<xsl:for-each select="parent/pair[count(. | key('pair-by-name', name)[1]) = 1]">
<xsl:sort select="name" />
<pair>
<name>
<xsl:value-of select="name"/>
</name>
<value>
<xsl:value-of select="sum(key('pair-by-name', name)/value)"/>
</value>
</pair>
</xsl:for-each>
</parent>
</xsl:template>
上面的代码应该可以工作。